The Spiritual Automaton in the Transpersonal Spacetime of Class Struggle: Pietro Marcello’s Martin Eden - Mecchia, Giuseppina (Quaderni d'Italianistica, 2025)
Pietro Marcello’s film Martin Eden (2019) was received by critics and the public alike as an innovative approach to adaptation, launching a marginal director of socially engaged documentaries onto the international cinema scene. In this essay, I discuss the political implications of a film that scrambles temporal and spatial references in its reprisal of Jack London’s 1909 eponymous classic, transposing its setting from San Francisco to Naples and expanding its historical reach from a main temporality going from the 1910s to the early 1980s. I argue that Marcello uses the posthuman sensibilities allowed by writing, recording, and filming techniques to reveal the transtemporal nature of class struggle. As a successful writer, Martin Eden finally understands that what the ruling classes cannot tolerate is not only economic but also intellectual and artistic emancipation.